Investigating the Potential for Increased Energy Utilisation and Reduced CO2 Emissions at Mo Industrial Park - Torbjørn Pettersen; Emil Dæhlin; Per Anders Eidem; Olaf Trygve Berglihn (Energies, 2020)
The potential for increased energy utilisation and reduced carbon footprint has been investigated for the industrial park Mo Industri Park (MIP), located at Mo i Rana, Norway. Process data has been gathered to quantify the energy flows between industrial clients. The energy flows have been visualised quantitatively in Sankey diagrams, while the quality of the available energy is presented in the form of a grand composite curve. High temperature flue gas from ferrosilicon (FeSi) production at Elkem Rana represent the largest heat source available for utilisation. A theoretical assessment of potential applications for this energy is presented and includes: (1) electricity production; (2) local biocarbon production, where surplus heat is utilised for drying of wood chips; (3) post combustion carbon capture, where surplus heat is utilised for solvent regeneration. The results indicate that increasing the current energy recovery from 400 GWh to >640 GWh is realistic. The increase in energy recovery can be used for reducing the carbon footprint of the industrial park. Investment in a common utility network for surplus heat may lower the threshold for establishing other energy clients at MIP. These are possibilities which may be investigated in more detail in future work.